Small worlds : 60 moons of the solar system - Kelch, Joseph W., 1958- (New York : Prentice-Hall Books for Young Readers, 1987)
Discusses the origin and characteristics of each of the moons circling the planets of the solar system and presents information on both manned and unmanned space exploration.
Includes index.
Keywords: Satellites -- Juvenile literature; Satellites; Outer space -- Exploration -- Juvenile literature; Outer space -- Exploration